Análise da influência do design da prótese e tratamento de superfície de parafusos na retenção e estabilidade de próteses parciais sobre implantes: análise in vitro - Pinto, Leandro Moreira (2015)
The aim of this study was to assess the effect of DLC (Diamond Like Carbon) coating of prefabricated implant screw on removal torque before and after cyclic load. The properties of DLC films, including hardness, wear resistance, chemical stability, and biocompatibility, are similar to those diamond materials. Four groups with two crowns supported by two implants (n=5) were obtained according to prosthesis Splinted and Non- Splinted with Titanium and DLC coating screw (STi, SC, NSTi e NSC). The prosthetic screws were tightened with 32Ncm, using a hexagonal wrench. The screws were retightening and the samples submitted to 106 mechanical cycles (4Hz/98N). After cyclic load, loosening torque were evaluating. The final measurements were performed and the results submitted to 3-way - Anova/Tukey’s. Negative correlation was observed between Non-Splinted prostheses and titanium screw as loosening torque of prosthetic screws, the coating screw showed better performance on both set of prostheses under cyclic load (P= 0,017). Conclusion, the DLC coating should be indicated for single crowns because it showed better performance than titanium screw.